2003
DOI: 10.3354/meps253055
|View full text |Cite
|
Sign up to set email alerts
|

Variation in community structure within hydrothermal vent mussel beds of the East Pacific Rise

Abstract: Patterns in invertebrate community structure associated with mussel beds at 3 hydrothermal vents on the northern East Pacific Rise (NEPR) were explored using quantitative, replicate sampling methods and were compared to those of southern East Pacific Rise (SEPR) mussel beds (~3000 km apart). Univariate measures of diversity (H ', J ') did not differ among 3 NEPR mussel beds. Diversity by most estimates was lower at NEPR mussel beds than at SEPR mussel beds. Invertebrate faunas of NEPR and SEPR mussel beds belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 47 publications
6
68
1
Order By: Relevance
“…Site differences for vent assemblages situated just a few kilometers apart are now well documented and have been correlated with factors such as the age of the biogenic habitat that de fines the assemblage (e.g. Van Dover 2003, Dreyer et al 2005. Multi variate analyses indicated that peripheral vent fauna of Solwara 1 and South Su samples were well differentiated from the active vent assemblages (presence− absence data).…”
Section: Discussionmentioning
confidence: 96%
“…Site differences for vent assemblages situated just a few kilometers apart are now well documented and have been correlated with factors such as the age of the biogenic habitat that de fines the assemblage (e.g. Van Dover 2003, Dreyer et al 2005. Multi variate analyses indicated that peripheral vent fauna of Solwara 1 and South Su samples were well differentiated from the active vent assemblages (presence− absence data).…”
Section: Discussionmentioning
confidence: 96%
“…This technique risks possible loss of macrofaunal individuals through winnowing compared with the closed bag technique of the pot samplers. Consequently, scoop samples have previously been included in analyses of macrofaunal species richness but excluded from multivariate analyses of macrofaunal composition (Van Dover & Trask, 2000;Van Dover, 2002;Dorries & Van Dover, 2003;Turnipseed et al, 2003;Van Dover, 2003;Dreyer et al, 2005). The abundance of nematodes per litre of mussel volume, however, is actually greater in scoop samples than pot samples, indicating that this meiofaunal taxon is resistant to any winnowing effect.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…The macrofaunal assemblages of young (<6 y) and old (>8 y) mussel beds could also be distinguished by multivariate analysis (Van Dover, 2003;Dreyer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The prevailing view, however, is that vent communities are unstable, varying dramatically in composition and structure over time, with especially rapid transitions during the commencement and cessation of fluid flow (e.g. Tunnicliffe et al 1997, Shank et al 1998, Mullineaux et al 2000, 2003, Tsurumi & Tunnicliffe 2001. The least stable vent communities reported to date may be those associated with large sulfide edifices in vent fields on the Juan de Fuca ABSTRACT: Comparisons of macrofaunal community structure (species composition, abundance, biovolume, rank order, species richness, diversity) in hydrothermal vent mussel beds at 9°50' N (9N) on the East Pacific Rise were made from analysis of multiple quantitative samples collected in 1999 and 2001 from each of 3 mussel beds of known age (4 to 8 yr in 1999).…”
Section: Introductionmentioning
confidence: 99%